Methylene Blue–Mediated Antimicrobial ​Photodynamic Therapy Against Clinical Isolates of Extensively Drug Resistant ​Gram-Negative Bacteria Causing Nosocomial Infections in Thailand, An In Vitro Study - Chankiat Songsantiphap; Jakapat Vanichanan; Tanittha Chatsuwan; Tanittha Chatsuwan; Pravit Asawanonda; Einapak Boontaveeyuwat (Frontiers in Cellular and Infection Microbiology, 2022)
Background/PurposeSome multidrug-resistant gram-negative bacteria as a global threat have been recently prioritized for research and development of new treatments. We studied the efficacy of methylene blue–mediated antimicrobial photodynamic therapy (MB-aPDT) for the reduction of extensively drug-resistant Acinetobacter baumannii (XDR-AB) and Pseudomonas aeruginosa (XDR-PS) and multidrug-resistant Klebsiella pneumoniae (MDR-KP) isolated in a university hospital setting in Thailand.MethodTwo isolates of each selected bacterium were collected, XDR-AB1 and AB2, XDR- PS1 and PS2, and MDR-KP1 and KP2. Three triplicate experiments using various MB concentrations alone, various red light fluences alone, as well as the selected non-toxic doses of MB and fluences of red light combined as MB-aPDT were applied on each selected isolate. The colonies were counted [colony forming units (CFU)/ml]. Estimation of the lethal treatment dose defined as reduction of > 2 log10 in CFU/ml compared with untreated bacteria.ResultThere were generally negligible changes in the viable counts of the bacterial suspensions treated with all the MB concentrations (p > 0.05). In the second experiment with the only red light treatments, at fluences higher than 2 J/cm, reduction trend in viable counts across all the isolates was observed. Only for MDR-KP1, however, the lethal dose was achieved with the highest fluence of red light (80 J/cm). With the concentration of MB, 50 and 150 mg/L in the third experiment (MB-aPDT), the greater bacterial reduction was observed in all clinical isolates leading to their lethal viable cell reduction when escalating the light fluence to 80 J/cm.ConclusionsMB-aPDT evidently killed the selected XDR and MDR-gram negative bacteria. In highly drug-resistant crisis era, MB-aPDT could be a promising option, particularly for local infections and infection complicating chronic wounds.